Teacher leadership that strengthens professional practice - Danielson, Charlotte (Alexandria, VA : Association for Supervision and Curriculum Development, 2006)
Offers teachers and administrators practical tips to help them better support the development of outstanding teacher leaders who are committed to helping their students through informal and voluntary leading efforts.
Leadership stories -- What is teacher leadership? -- What do teacher leaders do? -- School culture -- Schoolwide policies and programs -- Teaching and learning -- Communications and community relations -- Promoting teacher leadership -- The skills of teacher leadership -- Appendix: school audit.
Includes bibliographical references (p. 154-155) and index.
Professional
Keywords: Educational leadership; Teacher participation in administration; Teachers -- Professional relationships; Leadership; Teachers